2010
DOI: 10.1063/1.3502603
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of the free excitons in CuInSe2 single crystals

Abstract: High-quality CuInSe2 single crystals were studied using polarization resolved photoluminescence (PL) and magnetophotoluminescence (MPL). The emission lines related to the first (n=2) excited states for the A and B free excitons were observed in the PL and MPL spectra at 1.0481 meV and 1.0516 meV, respectively. The spectral positions of these lines were used to estimate accurate values for the A and B exciton binding energies (8.5 meV and 8.4 meV, respectively), Bohr radii (7.5 nm), band gaps (E-g(A)=1.050 eV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…The increasing cost and limited availability of indium, one of the main components in CuInSe 2 -based thin film solar cells, has resulted in a growing interest in the related semiconductor compounds Cu 2 ZnSn(S,Se) 4 whose crystalline structure is similar to chalcopyrite with In substituted by alternating zinc (Zn) and tin (Sn). The possibility of p-type doping by intrinsic defects and a high absorption coefficient, exceeding 10 4 cm -1 , in the visible range [1], make this new compound attractive for the application as an absorber layer in thin film solar cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing cost and limited availability of indium, one of the main components in CuInSe 2 -based thin film solar cells, has resulted in a growing interest in the related semiconductor compounds Cu 2 ZnSn(S,Se) 4 whose crystalline structure is similar to chalcopyrite with In substituted by alternating zinc (Zn) and tin (Sn). The possibility of p-type doping by intrinsic defects and a high absorption coefficient, exceeding 10 4 cm -1 , in the visible range [1], make this new compound attractive for the application as an absorber layer in thin film solar cells.…”
mentioning
confidence: 99%
“…The most efficient technique for gaining such knowledge is optical spectroscopy [3][4][5]. However, the usefulness of such methods depends critically on the availability of high quality material, with sharp and resolved features in the optical spectra.…”
mentioning
confidence: 99%
“…18 The determined C exciton ground state (l ¼ 0) binding energy at zero field E b (C) ¼ Ry so *(0,0) ¼ 8.5 meV is very close to E b for A and B of 8.5 and 8.4 meV, respectively. 8 Subtracting 8.5 meV from E g (C) the spectral position of the C exciton can be calculated as 1.2743 eV which is close to the experimentally observed value of 1.2750 eV in the zero field absorption spectrum in Fig. 1.…”
mentioning
confidence: 61%
“…Early optical spectroscopy studies of the excitonic properties of CuInSe 2 revealed the complexity of the valence band, which is split into A, B, and C sub-bands by the simultaneous influence of the non-cubic crystal field and spin-orbit coupling. 5 Recently, the excitonic studies were extended by works based on new advances in the material structural quality [6][7][8][9] determining accurate values of the A and B exciton binding energies E b 7 and hole effective masses. 9 Significantly fewer papers however are concerned with the C exciton, although the C-band parameters are necessary for the development of kp theory in the chalcopyrites.…”
mentioning
confidence: 99%
“…These values are close to E a1 , the thermal depth of w1, suggesting than the hole in the w1 exciton can be associated with either A or B sub-band. Both E a1 and E a2 are significantly greater than the binding energies of the A and B free excitons of 8.5 and 8.4 meV, 33,34 respectively, indicating that the w1 exciton is formed not by the capture of free excitons but by the capture of separate charge carriers. The two activation energies can be related to the localisation energies of the captured electron and hole.…”
Section: Temperature Dependence Of the W-linesmentioning
confidence: 99%